Cayenne Pepper Seed Partnership Sustainability Strategy (Case Study of "You Seed" Company Jember East Java) - Alfina Uswatun Hasanah; Sudarko Sudarko; Luh Putu Suciati (Buletin Penelitian Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Haluoleo, 2024)
Jember is one of the Cayenne pepper-producing districts in East Java. It is among the top 10 cayenne pepper producers in East Java and has the potential to contribute raw materials for cayenne pepper seeds. One of the superior seed-producing companies in Jember Regency is PT. Benih Unggul Sejati or You Seed Company. The company partners with cayenne pepper farmers in Jember to get raw seed materials. The higher demand for seeds is a problem, namely the farmers' lack of raw seed materials in stock. Farmers often provide seeds from their cayenne pepper harvest in quantities below the target set by the company. The sampling method uses a total sampling of 28 respondents. The data collection method uses observation, interview, and literature study methods. The research methods used are descriptive and quantitative. The results of the study are the sustainability strategy of the partnership that exists between the company PT. Benih Unggul Sejati and cayenne pepper seed farmers, namely the company strengthening emotional relationships with partner farmers through increasing the frequency of visits to partner farmers' land; the company provides capital loan assistance of up to 50% of the total cost of cayenne pepper farming expenses to partner farmers; utilizing waring technology in the cayenne pepper cultivation process; expanding the sales market for cayenne pepper seeds both nationally and internationally and cooperating with fellow IPBH member companies.